395 Post-cone residual disease in microinvasive cervical cancer: importance of surgical margin. (13th November 2020) - Cervantes, P; Altamirano, R; Nazzal, O; Solari, M; Pincheira, E; Rojas, J; Suarez, E
Abstract : Introduction: Microinvasive diseases of the cervix are conventionally treated with radical hysterectomy after confirmation of invasion depth and lymphovascular invasion in excisional biopsy. In some cases conization could be the definitive treatment in patients who wish to preserve fertility, it is essential to know the state of the section margins. The objective of this presentation is to demonstrate the risk of residual disease with cone positive margins. Methods: Retrospective review of patients with microinvasive cervical cancer between December 2014 and February 2020. The contact of the lesion directly with the edge of the cone was taken as positive margin, we compared results of cone biopsies and hysterectomies. Results: The study included 47 patients (median age 42.9). Diagnoses of microinvasive cervical cancer: insitu adenocarcinoma, (FIGO IA1 and IA2), histological: adenocarcinoma and squamous. 42 patients met the inclusion criteria (cone biopsy and hysterectomy). 30 (71%) with squamous cancer and 12 (29%) with adenocarcinoma. In 30 patients with squamous types, 14 cones had a positive margins, from which 10 (71%) surgical specimens resulted with residual disease, and 16 cones with negative margins, from which 1 (6.25%) specimen resulted with residual disease. In 12 patients with adenocarcinoma, there were 8 cones with positive margins, 6 (75%) surgical pieces were found with residual disease; 4 cones with negative margins, 3 (75%) surgical pieces were found with residual disease. Conclusions: Patients with positive margins regardless of histologic type are at increased risk for residual disease and is clearly more risky in adenocarcinomas due to multifocality.